El impacto territorial del sector turístico en el desarrollo del estado de Michoacán, 1990 – 2008 - Figueroa Aguilar, Marcela (Universidad Michoacana de San Nicolás de Hidalgo, 2011)
In the last dates the tourism has had a great importance inside the economy of the world and of the countries, Mexico is not foreign to this influence, where one has seen that the tourism has increased year with year, of the same way, Michocán's condition considers to the tourism as one of his economic principal branches, is for it that the question of investigation is which is the influence of the tourism in the regional development of Michoacán's condition in the years from 1990 to 2008; by what in this work there is analyzed the relation that exists between the tourism and the development, to be able to answer the hypothesis that appeared stocks in if the tourism affects the regional development of Michoacán's condition, considering to the development as an indicator of a better standard of living of the inhabitants of the locality, in the period of 1990 - 2008; as well as if the tourist activity is an element necessary for the continuity of the regional development of Michoacán's condition; and if the infrastructure of the sector tourism that offers the condition has strengthened the development of the tourist activity in the entity during this period; for such an end, the theoretical frame is checked in the variables of tourism and development, studying the concepts of development for which different authors arranged an appointment and one concluded that the development is the aptitude to generate prosperity that is translated in wellbeing not only economically but also socially from the inhabitants.

En últimas fechas el turismo ha tenido una gran importancia dentro de la economía del mundo y de los países, México no es ajeno a esta influencia, en donde se ha visto que el turismo ha aumentado año con año, de esa misma manera, el estado de Michoacán considera al turismo como una de sus ramas económicas principales, es por ello que la pregunta de investigación es cuál es la influencia del turismo en el desarrollo regional del estado de Michoacán en los años de 1990 a 2008; por lo que en este trabajo se analiza la relación que existe entre el turismo y el desarrollo, para poder contestar la hipótesis que se planteó basada en si el turismo impacta en el desarrollo regional del estado de Michoacán, considerando al desarrollo como un indicador de un mejor nivel de vida de los habitantes de la localidad, por el período de 1990 – 2008; así como si la actividad turística es un elemento necesario para la continuidad del desarrollo regional del estado de Michoacán; y si la infraestructura del sector turismo que ofrece el estado ha fortalecido el desarrollo de la actividad turística en la entidad durante ese período; para tal fin, se revisa el marco teórico en las variables de turismo y desarrollo, estudiando los conceptos de desarrollo para lo cual se citaron diferentes autores y se concluyó que el desarrollo es la capacidad para generar prosperidad que se traduzca en bienestar no solamente económico sino también social de los habitantes.
Instituto de Investigaciones Económicas y Empresariales. Doctorado en Ciencias del Desarrollo Regional
Keywords: http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/349; info:eu-repo/classification/cti/5; ININEE-D-2011-0001; Política turística; Desarrollo regional y turismo; Tipología del turismo; Gasto turístico; Divisas